Quantitative Research on the Effect of Natural Aging on the Mechanical Properties and Bake Hardening Properties of AA6014 Alloy within Six Months - Zhengwei Gu; Yuting Han; Ziming Tang; Lingling Yi; Ge Yu (Metals, 2021)
This article is dedicated to quantitatively and systematically revealing the changes of mechanical properties and bake hardening properties of AA6014 alloy during six-month natural aging in detail. Three directions (0, 45, and 90° relative to the rolling direction) of the aluminum alloy sheets and 16 time points within six months were selected to conduct experiments. The change trend of six mechanical properties (0.2% offset yield strength, ultimate tensile strength, plastic extension at maximum force, elongation after fracture, and strain hardening exponent) were obtained by a large number of micro-hardness measurements and tensile tests. The results show that elongations along the three directions are basically the same and do not drop significantly with the progress of natural aging but fluctuate within a certain range. The trends of the n value during natural aging before and after bake hardening are opposite and bake hardening leads to ~0.07 decrease of the n value. The PLC phenomenon disappears after 90 days of natural aging, and the yield strengths along the three directions also stabilize; thus, it can be inferred that the cluster changes tend to stabilize after 90 days natural aging. The large and systematic dataset are clearly and intuitively presented, which can not only be used to provide data reference for industrial production of automobile manufacturers but also be used to reveal the microscopic mechanism of the natural aging process.